The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1007/s40544-020-0378-z
|View full text |Cite
|
Sign up to set email alerts
|

Tribological behavior of ammonium-based protic ionic liquid as lubricant additive

Abstract: In this study, the tribological behavior of an ammonium-based protic ionic liquid (PIL) as an additive in a base mineral oil (MO) is investigated on a steel-steel contact at room temperature and 100 °C. Tri-[bis(2-hydroxyethylammonium)] citrate (DCi) was synthesized in a simple and low-cost way, and the ionic structure of DCi was confirmed by proton nuclear magnetic resonance (1H NMR). The stability measurement of 1 wt% DCi to a MO was investigated, and the lubricating ability and anti-wear properties of DCi a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…A large number of studies have shown that the lubrication performances of PEGbased lubricating oils are highly dependent on the lubricant additives, in particular the friction-reducing and anti-wear additives. With the rapid development of science technology, PEG-based lubricating oils are hard-pressed to meet increasingly harsh lubrication requirements of modern mechanical equipment such as super-high and/or ultra-low temperatures, extreme pressure, and high vacuum conditions, considerably limiting the further development of PEG-based lubricating oils [146,147]. Nanomaterials as additives to promote the friction-reducing and anti-wear properties of PEG-based lubricating oils have been repeatedly confirmed in the literature [66].…”
Section: Cqds As Additives In Pegmentioning
confidence: 99%
“…A large number of studies have shown that the lubrication performances of PEGbased lubricating oils are highly dependent on the lubricant additives, in particular the friction-reducing and anti-wear additives. With the rapid development of science technology, PEG-based lubricating oils are hard-pressed to meet increasingly harsh lubrication requirements of modern mechanical equipment such as super-high and/or ultra-low temperatures, extreme pressure, and high vacuum conditions, considerably limiting the further development of PEG-based lubricating oils [146,147]. Nanomaterials as additives to promote the friction-reducing and anti-wear properties of PEG-based lubricating oils have been repeatedly confirmed in the literature [66].…”
Section: Cqds As Additives In Pegmentioning
confidence: 99%
“…Despite these promising results, the implementation of ILs in oil formulations has been constrained by four main issues: (i) their high cost; (ii) the corrosivity of most ILs, which derives from the sensitivity of halogenated ILs to moisture that can result in the release of toxic and corrosive halogen halides [49][50][51][52]; (iii) the limited solubility of the vast majority of ILs in hydrocarbon uids; and (iv) our limited understanding of the IL lubrication mechanism(s), which has hampered our ability of rationally designing task-speci c ILs [53]. The rst three issues have progressively been solved over the last decade with: (i) the recent synthesis of airstable, eco-friendly, protic ILs (PILs), whose ease of preparation can signi cantly lower costs [54,55]; (ii) the transition towards halogen-free ILs, which has drastically decreased corrosion problems [56-65]; and (iii) the synthesis of oil-soluble ILs [31,61,[66][67][68][69][70][71][72] and the development of polymer-encapsulated ILs [53]. Despite these remarkable advancements, the underpinning lubrication mechanism of ILs is still under debate.…”
Section: Introductionmentioning
confidence: 99%
“…Energy consumption owing to friction accounts for 23%, approximately 119 EJ, of global energy consumption [1,2]. In present industrialized nations, financial wastage brought by friction and wear is as high as about 6% of GDP [1,3].…”
Section: Introductionmentioning
confidence: 99%